Bibliometric Analysis of Talent Development Through Mentoring - Simanjuntak, Edward Ignatius (West Science Interdisciplinary Studies, 2025)
This study aims to analyze the trends, patterns, and contributions of mentoring to talent development through a bibliometric approach. The analysis is conducted using various national and international literature that explores the relationship between mentoring programs and talent development across different contexts, including education, organizations, and professional development. The findings indicate that mentoring plays a significant role in enhancing the skills and competencies of human resources. To support the analysis, VOSviewer software was utilized to visualize keyword networks, author collaborations, and publication trends. This study is expected to provide a comprehensive overview of the strategic role of mentoring in sustainable talent development.